Assessment of learning with nature in preschool - Saleh, Syaida Farizah; Abdul Latip, Nurul Syala; Abdul Rahim, Asiah (Malaysian Institute of Planners, 2018)
Learning with nature is a form of psychological therapy for all, including children with disability. Beyond the psychological aspect, access to outdoor green space can also improve social, environmental, developmental, emotional and behavioural, and even medical outcomes. In Malaysia, studies of learning with nature remain scarce due to the Malaysian education system’s focus on indoor learning rather than outdoor learning. This research aimed at determining perceptions towards the application of learning with nature among preschool educators. Qualitative methods were used for data collection, consisting of structured interview and field observation. Four preschools were selected as sample. Results show that learning with nature contributes to the positive development of the children. The approaches used to instil nature awareness include conducive landscape, environmental activities, outdoor class activities, outdoor free play, formal education and recreational programme outside a preschool. These involved both outdoor and indoor spaces and facilities.